Positive pole piece and preparation method thereof, battery monomer, battery and electric device
By introducing dielectric material into the positive electrode sheet of lithium-ion battery, and using electric field excitation to generate an electroporated electric field, the problem of the battery being unable to fully charge at room temperature is solved, the battery charging speed and energy density are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202311416202.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
Existing lithium-ion batteries cannot fully charge to 100% SOC at room temperature, and it is easier to reach full charge in high-temperature environments, resulting in insufficient comprehensive performance of the battery.
A positive electrode sheet containing a dielectric material is used, and the dielectric constant of the dielectric material is 30 to 3000. The dielectric material is excited by the electric field to generate an electroporated electric field, and the Li+/Na+ active ions are driven to remove the positive electrode sheet, thereby improving the full charge effect and charging speed of the battery.
Improves the battery's capacity full charge performance at room temperature, improves charging speed and dynamic performance, extends the battery life, and improves the battery's energy density and voltage stability.
Smart Images

Figure CN119920815A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a positive electrode plate and a preparation method thereof, a battery cell, a battery and an electrical device. Background Art
[0002] In recent years, with the widespread application of battery cells represented by lithium-ion batteries, the performance of battery cells has received more and more attention.
[0003] During the charging process at room temperature, the active ions in the battery cells cannot completely escape from the positive electrode, resulting in the battery being unable to be fully charged to 100% SOC at room temperature, while it is easier to reach a full charge state in an environment above 40°C. Therefore, the comprehensive performance of the battery cells still needs to be improved. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode plate and a method for preparing the same, which can improve the degree of escape of active ions in the positive electrode plate during the charging and discharging process of the battery and improve the full charging effect of the battery; the present application also aims to provide a battery cell, a battery and an electrical device that can achieve the beneficial effects of the positive electrode plate.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode plate, which includes: a positive electrode collector and a positive electrode active material film layer arranged on at least one side of the positive electrode collector, the positive electrode active material film layer contains a positive electrode active material and a dielectric material, and the dielectric constant of the dielectric material is 30 to 3000.
[0006] According to the embodiment of the present application, the positive electrode active material film layer of the positive electrode sheet includes a dielectric material. The electric field formed by the battery during the charging and discharging process, the dielectric material is excited by the electric field. On the one hand, the positive and negative charges of the dielectric material are arranged separately to generate an electric polarization electric field. The dielectric constant of the dielectric material is within the above range, and the electric field force is within a suitable range, which can drive Li + / Na + The active ions escape from the positive electrode, accelerating the rate of active ion removal, improving the full-capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's kinetic performance.
[0007] In addition, as the battery is charged and discharged, the dissolved transition metal ions are enriched on the surface of the positive electrode, forming a Li + / Na +The reverse electric field for the escape of active ions, since the positive electrode active material film layer of the positive electrode plate contains dielectric material, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately to generate a polarization electric field. The dielectric constant of the dielectric material is within the above range, and the electric field force is within a suitable range, which can offset the electric field force formed by the enrichment of transition metal ions, thereby improving the lithium / sodium removal performance of the positive electrode plate, which is beneficial to the full charging performance of the battery at room temperature, improving the charging speed, and is beneficial to the battery's kinetic performance.
[0008] On the other hand, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, so it can store a certain amount of charge, which is beneficial to increase the battery capacity and energy density; because the dielectric material can store a certain amount of charge and form an electric polarization electric field, it reduces the battery voltage drop during the charge and discharge cycle, especially in high discharge rate or low temperature environment.
[0009] In some optional implementations, the dielectric constant of the dielectric material is 90-2000, and optionally 1200-1800.
[0010] According to the embodiments of the present application, the dielectric constant of the dielectric material is within the above range, which is conducive to the dielectric material storing more charge, improving the capacity of the battery, and increasing the energy density of the battery. It is also conducive to the dielectric material having good electrochemical stability, which can maintain low loss during the battery cycle charge and discharge process, improve the voltage stability of the battery, improve the charge and discharge rate of the battery, and extend the life of the battery.
[0011] In some optional embodiments, the dielectric material includes one or more of barium titanate, lead titanate, lithium niobate, lead zirconate titanate, lead metaniobate, lithium barium lead niobate, titanium zirconium oxide, zirconium ferrite, bismuth ferrite, barium strontium titanate, and zirconium titanate.
[0012] According to the embodiments of the present application, the above-mentioned types of dielectric materials have better polarization electric field energy excited by the battery, which improves the desolvation effect and charge transfer, is beneficial to reducing the DC resistance of the positive electrode plate, and improving the battery's charge and discharge performance and full capacity charging performance.
[0013] Optionally, the dielectric material includes one or more of lead barium lithium niobate, zirconium titanium oxide, zirconium ferrite, bismuth ferrite, barium strontium titanate, and zirconium titanate.
[0014] According to the embodiments of the present application, the above-mentioned dielectric materials have better polarization electric field energy stimulated by the battery, which is beneficial to reduce the DC resistance of the positive electrode plate and can drive Li + / Na +Active ions are removed from the positive electrode sheet, accelerating the removal rate of active ions and improving the battery's charge and discharge performance and full capacity performance. The above-mentioned types of dielectric materials can affect the size of the internal resistance when subjected to an electric field, thereby reducing the positive electrode sheet internal resistance (DCR) and improving the rapid charge and discharge performance of the battery containing the positive electrode sheet.
[0015] In some alternative embodiments, the dielectric material comprises a ferroelectric material.
[0016] According to the embodiment of the present application, when the ferroelectric material is subjected to the electric field, an electric polarization cell is generated, which is conducive to the deintercalation of active ions and improves the rapid charge and discharge performance of the battery containing the positive electrode sheet. When the ferroelectric material is subjected to the electric field, it can affect the size of the internal resistance, thereby inducing additional current flow, thereby reducing the internal resistance of the positive electrode sheet and improving the rapid charge and discharge performance of the battery containing the positive electrode sheet.
[0017] In some optional embodiments, the mass content of the dielectric material in the positive electrode active material film layer is 0.5% to 10%.
[0018] According to the embodiment of the present application, the mass content of the dielectric material in the positive electrode active material film layer is within the above range, which is conducive to the dielectric material forming a polarization electric field with an electric field force of appropriate magnitude, accelerating the deintercalation of active ions, and thus facilitating the improvement of the capacity and kinetic performance of the battery containing the positive electrode plate.
[0019] In addition, the mass content of the dielectric material in the positive electrode active material film layer is within the above range, and the appropriate electric field generated helps to suppress the aggregation of dissolved manganese ions on the cathode surface, which helps to improve the cycle stability of the electric field.
[0020] In some optional embodiments, the average particle size Dv of the dielectric material is 1 50Satisfies 1nm<Dv 1 50<1500nm, optionally, 10nm<Dv 1 50<1000nm.
[0021] According to the embodiment of the present application, controlling the particle size of the dielectric material within the above range can adjust its surface area, provide more active sites, store charge, and thus increase the capacity and energy density of the battery; it can provide a shorter electron transmission path, facilitate charge redistribution, and thus increase the capacity of the battery. In addition, controlling the particle size of the dielectric material within the above range is conducive to providing a more uniform electric field force, so that the active ions can be better deintercalated from the positive electrode active material, and smaller dielectric materials can increase the charging and discharging rates of the battery.
[0022] In some optional embodiments, at least a portion of the surface of the positive electrode active material includes a coating layer, and the coating layer includes a dielectric material.
[0023] According to the embodiment of the present application, the dielectric material forms a coating layer, which is coated on the surface of the positive electrode active material. On the one hand, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, generating an electric polarization electric field, which can drive Li + / Na + Active ions escape from the positive electrode sheet, accelerating the rate of active ion removal, improving the full capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's dynamic performance. On the other hand, the dielectric material forms a coating layer that can reduce the volume change rate of the positive electrode active material during the charge and discharge process. The dielectric material forms a coating layer that can maintain the stability of the positive electrode active material in the electrochemical cycle and can reduce the contact area between the positive electrode active material and the electrolyte, thereby being beneficial to the battery's cycle stability.
[0024] In some optional embodiments, the average particle size Dv of the positive electrode active material is 2 The ratio of 50 to the thickness d of the coating layer on the positive electrode active material is (2-120):1, and can be optionally (4-100):1.
[0025] According to the embodiment of the present application, by controlling the thickness of the coating layer, the mass content of the dielectric material in the positive electrode active material can be controlled. On the other hand, by controlling the thickness of the coating layer, the force of the polarization electric field can be controlled, thereby comprehensively controlling the Li + / Na + The rate at which active ions are removed from the positive electrode.
[0026] In some optional embodiments, at least a portion of the surface of the positive electrode active material includes a coating layer, and the coating layer includes a ferroelectric material.
[0027] According to the embodiment of the present application, the ferroelectric material forms a coating layer, which is coated on the surface of the positive electrode active material. On the one hand, the ferroelectric material is excited by the electric field, and the positive and negative charges of the ferroelectric material are arranged separately, generating an electric polarization electric field, which can drive Li + / Na + Active ions escape from the positive electrode sheet, accelerating the rate of active ion removal, improving the full capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's dynamic performance. On the other hand, the ferroelectric material forms a coating layer that can reduce the volume change rate of the positive electrode active material during the charging and discharging process, improve the structural stability of the positive electrode sheet, and thus be beneficial to the battery's cycle stability.
[0028] In some optional embodiments, the positive electrode active material includes one or more of a metal oxide material and an olivine positive electrode material; optionally, the metal oxide material includes one or more of a layered metal oxide material and a spinel-type material; optionally, the olivine positive electrode material includes a lithium iron manganese phosphate material.
[0029] According to the embodiments of the present application, the above-mentioned metal oxides generally have a higher active ion storage capacity. The above-mentioned types of metal oxides can embed and release more active ions, thereby providing a higher battery capacity. This allows the battery to store more electrical energy and have a longer service life. The high capacity characteristics of metal oxides result in a higher energy density in the battery. Layered transition metal oxides have a certain oxidizability, and the redox reaction that occurs therein is beneficial to the stability of the material structure, helps to reduce the structural changes and attenuation of the material, and thus prolongs the cycle life of the battery.
[0030] In some optional embodiments, the specific surface area of the positive electrode active material satisfies BET of 11 m 2 / g~17m 2 / g. The specific surface area of the positive electrode active material can be 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g or any value thereof. The specific surface area of the positive electrode active material is within the above range, so that it can be more fully mixed with the above dielectric material and other components in the positive electrode active material film layer, which is beneficial for the positive electrode active material in the positive electrode sheet to uniformly deintercalate active ions under the action of the electric field force formed by the dielectric material, thereby improving the deintercalation rate of active ions.
[0031] In some optional embodiments, the average particle size Dv of the positive electrode active material is 2 50 satisfies: 0.2μm~2μm.
[0032] According to the embodiment of the present application, the average particle size Dv of the positive electrode active material is 2 50 In the above range, it can be mixed with the above dielectric material and other components in the positive electrode active material film layer, and the positive electrode active material is dispersed more evenly, which, on the one hand, improves the flexibility and cohesion of the positive electrode active material film layer, reduces the surface fracture or cracking caused by winding or folding the positive electrode sheet containing the positive electrode active material film layer, and on the other hand, is conducive to the positive electrode active material to uniformly contact with the dielectric material and make the dielectric material store charge, form a polarization electric field, and improve the deintercalation rate of active ions.
[0033] According to the embodiment of the present application, the average particle size Dv of the positive electrode active material is 2 50 In the above range, it is beneficial to the uniform distribution of the positive electrode active material with the dielectric material coated on the surface, and reduces the local temperature change of the dielectric material under the electric field.
[0034] In some optional embodiments, the coating layer has a thickness d of 5 nm to 100 nm in the cross section of the positive electrode active material.
[0035] According to the embodiments of the present application, the thickness of the coating layer is controlled within the above range, and the cycle performance of the battery is improved while reducing the contact area between the positive electrode active material and the electrolyte.
[0036] In some optional embodiments, the positive electrode active material film layer includes a binder and a conductive agent. When the positive electrode active material film layer has a conductive agent or a binder, the positive electrode active material film layer has a certain cohesive strength, which can improve the flexibility of the positive electrode active material film layer, reduce the probability of fracture or cracking of the positive electrode active material film layer when winding or folding, and at the same time improve the conductivity of the positive electrode plate and reduce the internal resistance of the positive electrode plate.
[0037] In some optional embodiments, the conductive agent is conductive carbon black, and optionally, the average particle size Dv50 of the conductive carbon black is 10nm to 1μm, and optionally 50nm to 500nm. The average particle size Dv50 of the conductive carbon black is within the above range, and can be mixed with the above dielectric material and other components in the positive electrode active material film layer, and the conductive carbon black is more evenly dispersed, which improves the flexibility and cohesion of the positive electrode active material film layer on the one hand, and reduces the surface fracture or cracking caused by winding or folding of the positive electrode sheet containing the positive electrode active material film layer, and on the other hand, it is conducive to the conductive carbon black to uniformly contact with the dielectric material and realize the storage of charge, forming a polarization electric field to increase the deintercalation rate of active ions.
[0038] In some optional embodiments, based on the total mass of the positive electrode active material film layer, the positive electrode active material film layer includes: 85%-98.7% of the positive electrode active material, optionally 91.5%-98.3%.
[0039] The content of the positive electrode active material in the positive electrode active material film layer is within the above range, which is beneficial to increasing the capacity of the battery, improving the energy density of the battery, and thus comprehensively changing the performance of the battery.
[0040] In some optional embodiments, based on the total mass of the positive electrode active material film layer, the positive electrode active material film layer includes: 0.4% to 10% of the conductive agent, optionally 0.7% to 5%.
[0041] The content of the conductive agent in the positive electrode active material film layer is within the above range, which is beneficial to reducing the internal resistance of the positive electrode plate, reducing the internal resistance of the battery cell, facilitating the transfer of electrons, and improving the charge and discharge efficiency of the battery.
[0042] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, the method comprising:
[0043] Providing a slurry comprising a positive electrode active material and a dielectric material, wherein the dielectric constant of the dielectric material is 30 to 3000;
[0044] The slurry is coated on the positive electrode current collector to form a positive electrode active material film layer, thereby obtaining the positive electrode sheet of the first aspect.
[0045] According to the embodiment of the present application, in the preparation method of the positive electrode sheet, a slurry containing a dielectric material is used to form a positive electrode active material film layer. The electric field formed during the charge and discharge process of the battery excites the dielectric material by the electric field. On the one hand, the positive and negative charges of the dielectric material are arranged separately to generate an electric polarization electric field, thereby driving the Li + / Na + The active ions escape from the positive electrode, accelerating the rate of active ion removal, improving the full-capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's kinetic performance.
[0046] In addition, as the battery is charged and discharged, the dissolved transition metal ions are enriched on the surface of the positive electrode, forming a Li + / Na + The reverse electric field for the escape of active ions, since the positive electrode active material film layer of the positive electrode plate contains dielectric material, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, generating an electric polarization electric field, which can offset the electric field force formed by the enrichment of transition metal ions, thereby improving the lithium / sodium removal performance of the positive electrode plate, which is beneficial to the full charging performance of the battery at room temperature, improving the charging speed, and is beneficial to the battery's kinetic performance.
[0047] On the other hand, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, so it can store a certain amount of charge, which is beneficial to increase the battery capacity and improve the energy density of the battery; because the dielectric material can store a certain amount of charge, it is beneficial to improve the voltage stability of the battery and reduce the voltage drop during the charge and discharge cycle. This helps to maintain the voltage stability of the battery, especially at high discharge rates or low temperature environments.
[0048] In a third aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, the method comprising:
[0049] Providing a slurry containing a positive electrode active material, wherein at least a portion of the surface of the positive electrode active material includes a coating layer, the coating layer includes a dielectric material, and the dielectric constant of the dielectric material is 30 to 3000;
[0050] The slurry is coated on the positive electrode current collector to form a positive electrode active material film layer, thereby obtaining the positive electrode sheet of the first aspect.
[0051] According to the embodiment of the present application, in the preparation method of the positive electrode sheet, at least part of the surface of the positive electrode active material is coated with a dielectric material, which can also improve the de-lithiation / de-sodium performance of the positive electrode sheet, improve the full charging performance of the battery, increase the charging speed, and improve the dynamic performance of the battery. It can also increase the energy density of the battery, improve the voltage stability of the battery, and reduce the voltage drop during the charge and discharge cycle.
[0052] In a fourth aspect, an embodiment of the present application provides a battery cell, comprising the positive electrode sheet of the first aspect or the positive electrode sheet manufactured by the method of the second aspect or the third aspect.
[0053] In a fifth aspect, an embodiment of the present application provides a battery, comprising the battery cell of the fourth aspect.
[0054] In a sixth aspect, an embodiment of the present application provides an electrical device comprising the battery of the fifth aspect.
[0055] The embodiments of the present application provide a battery cell, a battery, and an electrical device that can achieve the beneficial effects of the positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0057] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0058] Figure 2 yes Figure 1 An exploded schematic diagram of a battery cell is shown.
[0059] Figure 3 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0060] In the drawings, the drawings are not necessarily drawn to scale. DETAILED DESCRIPTION
[0061] Below, the electrode assembly and its preparation method, battery cell, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0062] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0063] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0064] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0065] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0066] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0067] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0068] Unless otherwise specified, in this application, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0069] If not specifically stated otherwise, in this application, the term "attach" refers to connection by adhesion, coating or the like.
[0070] If not otherwise specified, in this application, the terms "first", "second", "third", "fourth", etc. are used to distinguish different objects rather than to describe a specific order or a primary and secondary relationship.
[0071] Unless otherwise specified, in this application, the term "active ions" refers to ions that can be inserted and removed back and forth between the positive and negative electrodes of a battery cell, including but not limited to lithium ions, sodium ions, etc.
[0072] The term "multiple" as used herein refers to two or more (including two). The term "multiple" or "several" as used herein refers to two or more (including two).
[0073] In the present application, the battery cell may include a lithium-ion battery, a sodium-ion battery, etc., which is not limited in the present embodiment. The battery cell may be an aqueous battery or an oil-based battery, which is not limited in the present embodiment. The battery cell may be a flat body, a rectangular parallelepiped, or other shapes, which is not limited in the present embodiment.
[0074] A battery cell can be a rechargeable battery or a storage battery, which refers to a battery that can be used continuously by recharging the active material after the battery is discharged. Generally, a battery cell includes an electrode assembly and an electrolyte, and the electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator.
[0075] Due to the material and structural characteristics of the positive electrode and electrolyte, the battery cannot be fully charged to 100% SOC during normal temperature charging, which greatly limits the performance of the battery and its application scenarios. The reason may be that the characteristics of the positive active material in the positive electrode and the ion conductivity of the electrolyte limit the rapid de-lithium / de-sodium performance of the battery, making it impossible to fully charge the battery at room temperature.
[0076] Research has found that the positive electrode sheet has a great influence on the full charge performance of the battery. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material film layer. The positive electrode active material film layer is coated on the surface of the positive electrode current collector, and the positive electrode active material film layer includes a positive electrode active material. Conventional positive electrode materials cannot completely release active ions including lithium ions stored in the positive electrode at room temperature, resulting in the battery being unable to be fully charged at room temperature, reducing the battery capacity.
[0077] Furthermore, the positive electrode active material generally contains transition metal elements. During the battery charging and discharging process, the transition metal elements will be dissolved with the charge and discharge cycle, such as forming manganese ions; the dissolved transition metal ions are enriched on the surface of the positive electrode, forming a Li + / Na + The reverse electric field caused by the escape of active ions further reduces the delithiation / desodium performance of the positive electrode, thereby affecting the full charging performance of the battery.
[0078] After research, it is found that one of the effective ways to solve the above-mentioned problem includes providing a positive electrode plate to improve the full charging performance of a battery containing the positive electrode plate.
[0079] Positive electrode
[0080] In a first aspect, an embodiment of the present application provides a positive electrode plate, which includes: a positive electrode collector and a positive electrode active material film layer arranged on at least one side of the positive electrode collector, the positive electrode active material film layer contains a positive electrode active material and a dielectric material, and the dielectric constant of the dielectric material is 30 to 3000.
[0081] Dielectric materials are insulating materials that can be polarized at room temperature. Their main characteristics are high resistivity and electrical insulation. The charged particles in dielectric materials are tightly bound by the internal forces of atoms and molecules or the forces between molecules and cannot conduct current freely. Under the action of an external electric field, dielectric materials will undergo electric field polarization, that is, positive and negative charges are arranged separately, generating a polarized electric field.
[0082] When the dielectric constant of the dielectric material is 30 to 3000, it can provide an electric field force of appropriate size, which not only accelerates the removal rate of active ions, but also does not significantly reduce other performance of the battery. The detection method of the dielectric constant can be a commonly used method in the field, such as a series method and a reflection method. As an example, the series method is a common dielectric constant measurement method, which uses the impedance characteristics of series capacitors to measure the constant of the dielectric.
[0083] According to the embodiment of the present application, the positive electrode active material film layer of the positive electrode sheet includes a dielectric material. The electric field formed by the battery during the charging and discharging process, the dielectric material is excited by the electric field. On the one hand, the positive and negative charges of the dielectric material are arranged separately to generate an electric polarization electric field. The dielectric constant of the dielectric material is within the above range, and the electric field force is within a suitable range, which can drive Li + / Na + Active ions escape from the positive electrode, accelerating the rate of active ion removal, improving the full capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's dynamic performance. In addition, as the battery charges and discharges, the dissolved transition metal ions are enriched on the surface of the positive electrode, forming a Li + / Na + The reverse electric field for the escape of active ions, since the positive electrode active material film layer of the positive electrode plate contains dielectric material, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately to generate a polarization electric field. The dielectric constant of the dielectric material is within the above range, and the electric field force is within a suitable range, which can offset the electric field force formed by the enrichment of transition metal ions, thereby improving the lithium / sodium removal performance of the positive electrode plate, which is beneficial to the full charging performance of the battery at room temperature, improving the charging speed, and is beneficial to the battery's kinetic performance.
[0084] On the other hand, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, so it can store a certain amount of charge, which is beneficial to increase the battery capacity and energy density; because the dielectric material can store a certain amount of charge and form an electric polarization electric field, it reduces the battery voltage drop during the charge and discharge cycle, especially in high discharge rate or low temperature environment.
[0085] Furthermore, the positive electrode active material is LiMn x Fe1-x PO4, where 0<x<1. When the positive electrode active material is lithium iron manganese phosphate, the promoting effect on the full charging performance of the battery at room temperature is more obvious.
[0086] It is worth noting that the positive electrode active material film layer of the positive electrode plate includes a dielectric material, which takes into account the cycle stability of the battery including the positive electrode plate, thereby improving the full charging performance and dynamic performance of the battery while taking into account the cycle stability of the battery.
[0087] In some optional implementations, the dielectric constant of the dielectric material is 90-2000, and optionally 1200-1800.
[0088] Optionally, the dielectric constant of the dielectric material can be any value or a range thereof among 30, 40, 50, 60, 70, 80, 90, 100, 100, 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000.
[0089] According to the embodiments of the present application, the dielectric constant of the dielectric material is within the above range, which is conducive to the dielectric material storing more charge, improving the capacity of the battery, and increasing the energy density of the battery. It is also conducive to the dielectric material having good electrochemical stability, which can maintain low loss during the battery cycle charge and discharge process, improve the voltage stability of the battery, improve the charge and discharge rate of the battery, and extend the life of the battery.
[0090] In some optional embodiments, the dielectric material includes one or more of barium titanate, lead titanate, lithium niobate, lead zirconate titanate, lead metaniobate, lithium barium lead niobate, titanium zirconium oxide, zirconium ferrite, bismuth ferrite, barium strontium titanate, and zirconium titanate.
[0091] According to the embodiments of the present application, the above-mentioned types of dielectric materials have better polarization electric field energy stimulated by the battery, which is beneficial to reduce the DC resistance of the positive electrode plate and improve the charging and discharging performance and full capacity charging performance of the battery.
[0092] As an example, barium titanate can be a tetragonal crystal. When the substance in the positive electrode active material is detected by X-ray diffraction, the position of the 2θ characteristic peak of the X-ray diffraction peak of barium titanate includes any one or more of 22°, 31°, 38°, 45°, 56°, and 66°. The position of the 2θ characteristic peak of the X-ray diffraction peak of lead titanate includes any one or more of 21°, 22°, 31°, 32°, 39°, 43°, 46°, 49°, 51°, 55°, 57°, 65°, and 72°. The position of the 2θ characteristic peak of the X-ray diffraction peak of lithium niobate includes any one or more of 23°, 32°, 34°, 48°, 53°, and 55°. The position of the 2θ characteristic peak of the X-ray diffraction peak of lead zirconate titanate includes any one or more of 21°, 22°, 31°, 44°, 50°, and 56°. The position of the 2θ characteristic peak of the X-ray diffraction peak of lead metaniobate includes any one or more of 28°, 29°, 33°, 47°, 57°, and 61°.
[0093] In some optional embodiments, the dielectric material includes one or more of lead barium lithium niobate, zirconium titanium oxide, zirconium ferrite, bismuth ferrite, barium strontium titanate, and zirconium titanate.
[0094] According to the embodiment of the present application, the above-mentioned ferroelectric material has better polarization electric field energy stimulated by the battery, which is beneficial to reduce the interface impedance of the positive electrode plate and can drive Li + / Na + The active ions are removed from the positive electrode, which accelerates the removal rate of the active ions and improves the battery's room temperature charging and discharging performance and full capacity charging performance.
[0095] In some alternative embodiments, the dielectric material comprises a ferroelectric material.
[0096] Ferroelectric Materials: Ferroelectric materials are a class of materials with ferroelectric properties. Ferroelectricity refers to the ability of materials to produce spontaneous electric polarization under the action of an electric field and have positive and negative polarization states.
[0097] According to the embodiment of the present application, when the ferroelectric material is subjected to the electric field, an electric polarization cell is generated, which is conducive to the deintercalation of active ions and improves the rapid charge and discharge performance of the battery containing the positive electrode sheet. When the ferroelectric material is subjected to the electric field, it can induce additional current flow, thereby reducing the internal resistance of the positive electrode sheet and improving the rapid charge and discharge performance of the battery containing the positive electrode sheet.
[0098] In some optional embodiments, the mass content of the dielectric material in the positive electrode active material film layer is 0.5% to 10%.
[0099] Optionally, the positive electrode active material film layer contains a mass content of 0.5%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, Dielectric materials having any numerical value or composition range of 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, and 10.0%.
[0100] According to the embodiment of the present application, the mass content of the dielectric material in the positive electrode active material film layer is within the above range, which is conducive to the dielectric material forming a polarization electric field with an electric field force of appropriate magnitude, accelerating the deintercalation of active ions, and thus facilitating the improvement of the capacity and kinetic performance of the battery containing the positive electrode plate.
[0101] In addition, the mass content of the dielectric material in the positive electrode active material film layer is within the above range, and the appropriate electric field generated helps to suppress the aggregation of dissolved manganese ions on the cathode surface, which helps to improve the cycle stability of the electric field.
[0102] In some optional embodiments, the average particle size Dv of the dielectric material is 1 50Satisfies 1nm<Dv 1 50<1500nm, optionally, 10nm<Dv 1 50<100nm.
[0103] Optionally, the average particle size Dv of the dielectric material 1 50 can be any value or a range of its composition among 1.01nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 99.5nm, 120nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, and 1499nm.
[0104] According to the embodiments of the present application, controlling the particle size of the dielectric material within the above range can adjust its surface area, provide more active sites, store charge, and thus increase the capacity and energy density of the battery; it can provide a shorter electron transmission path, facilitate charge redistribution, and thus increase the capacity of the battery. In addition, controlling the particle size of the dielectric material within the above range is conducive to providing a more uniform electric field force, so that the active ions can be better deintercalated from the positive electrode active material, and smaller dielectric materials can increase the charging and discharging rates of the battery. By adjusting the particle size of the ferroelectric material within the above range, the electrochemical stability of the battery can be improved, the voltage fluctuation can be reduced, and it helps the battery maintain more stable performance under different operating conditions.
[0105] According to the embodiment of the present application, the average particle size Dv of the dielectric material is 1 50 In the above range, it is beneficial to the uniform distribution of the dielectric material in the positive electrode active material film layer, and reduces the local temperature change of the dielectric material under the electric field.
[0106] In some optional embodiments, at least a portion of the surface of the positive electrode active material includes a coating layer, and the coating layer includes a dielectric material.
[0107] According to the embodiment of the present application, the dielectric material forms a coating layer, which is coated on the surface of the positive electrode active material. On the one hand, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, generating an electric polarization electric field, which can drive Li + / Na + Active ions escape from the positive electrode sheet, accelerating the rate of active ion removal, improving the full capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's dynamic performance. On the other hand, the dielectric material forms a coating layer that can reduce the volume change rate of the positive electrode active material during the charge and discharge process. The dielectric material forms a coating layer that can maintain the stability of the positive electrode active material in the electrochemical cycle and can reduce the contact area between the positive electrode active material and the electrolyte, thereby being beneficial to the battery's cycle stability.
[0108] In some optional embodiments, the average particle size Dv of the positive electrode active material is 2 The ratio of 50 to the thickness d of the coating layer on the positive electrode active material is (2-120):1, and can be optionally (4-100):1.
[0109] Optionally, the average particle size Dv of the positive electrode active material 2The ratio of 50 to the thickness d of the coating layer in the cross section of the positive electrode active material is 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33 :1,34:1,35:1,36:1,37:1,38:1,39:1,40:1,41:1,42:1,43:1,44:1,45:1,46:1,47:1,48:1,49:1,50:1,55:1,60:1,65:1,70:1,75:1,80:1,85:1,90:1,95:1,100:1,105:1,110:1,115:1,120:1 any value or its composition range.
[0110] According to the embodiment of the present application, by controlling the thickness of the coating layer, the mass content of the dielectric material in the positive electrode active material can be controlled. On the other hand, by controlling the thickness of the coating layer, the force of the polarization electric field can be controlled, thereby comprehensively controlling the Li + / Na + The rate at which active ions are removed from the positive electrode.
[0111] In some optional embodiments, at least a portion of the surface of the positive electrode active material includes a coating layer, and the coating layer includes a ferroelectric material.
[0112] According to the embodiment of the present application, the ferroelectric material forms a coating layer, which is coated on the surface of the positive electrode active material. On the one hand, the ferroelectric material is excited by the electric field, and the positive and negative charges of the ferroelectric material are arranged separately, generating an electric polarization electric field, which can drive Li + / Na + Active ions escape from the positive electrode sheet, accelerating the rate of active ion removal, improving the full capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's dynamic performance. On the other hand, the ferroelectric material forms a coating layer that can reduce the volume change rate of the positive electrode active material during the charging and discharging process, improve the structural stability of the positive electrode sheet, and thus be beneficial to the battery's cycle stability.
[0113] Finally, when ferroelectric materials are subjected to an electric field, they produce polarized batteries. This change triggers additional current flow, which can reduce the internal resistance (DCR) of the positive electrode sheet and improve the fast charging and discharging performance of the battery containing the positive electrode sheet.
[0114] In some optional embodiments, the positive electrode active material includes one or more of a metal oxide material and an olivine positive electrode material; optionally, the metal oxide material includes one or more of a layered metal oxide material and a spinel-type material; optionally, the olivine positive electrode material includes a lithium iron manganese phosphate material.
[0115] The positive electrode active material film layer includes a positive electrode active material, and the positive electrode active material may be a positive electrode active material for a battery cell known in the art.
[0116] In some optional embodiments, the metal oxide comprises a structural formula A a Ni b Co c Mn f M d O e A metal oxide, wherein 0.5≤a≤1.2, 0≤b≤2, 0≤c≤2, 0≤f≤1, 0≤d≤1.5, 1≤e≤4, A includes one or more of Li and Na; M includes one or more of Ca, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B; optionally, b+c+d+f=1 or b+c+d+f=2; optionally, A also includes K. In some optional embodiments, a+2b+2c+2f+2d-2e=0 or a+2b+2c+4f+2d-2e=0 or a+2b+2c+3f+2d-2e=0.
[0117] According to the embodiments of the present application, the above-mentioned metal oxides generally have a higher active ion storage capacity. The above-mentioned types of metal oxides can embed and release more active ions, thereby providing a higher battery capacity. This allows the battery to store more electrical energy and have a longer service life. The high capacity characteristics of metal oxides result in a higher energy density in the battery. Layered transition metal oxides have a certain oxidizability, and the redox reaction that occurs therein is beneficial to the stability of the material structure, helps to reduce the structural changes and attenuation of the material, and thus prolongs the cycle life of the battery.
[0118] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0119] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0120] In some alternative embodiments, the chemical formula of the lithium iron manganese phosphate material may be LiMn x1 Fe 1-x1 PO4, LiNi x2 CoyMn z O2, LiFePO4, or at least one of them; wherein, 0 < x1 < 1, x2 + y + z = 1. The lithium iron manganese phosphate material crystal may be one or more of single crystal or polycrystal.
[0121] For example, when the battery cell is a lithium-ion battery cell or a lithium metal battery cell, the positive electrode active material may include one or more of lithium transition metal oxides, lithium-containing phosphates with olivine structure, and their respective modified compounds. Examples of the lithium transition metal oxides may include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphates with olivine structure may include one or more of lithium iron phosphate, composite materials of lithium iron phosphate and carbon, lithium manganese phosphate, composite materials of lithium manganese phosphate and carbon, lithium iron manganese phosphate, composite materials of lithium iron manganese phosphate and carbon, and their respective modified compounds. This application is not limited to these materials, and other conventionally well-known materials that can be used as the positive electrode active material may also be used.
[0122] In some embodiments, in order to further improve the energy density of the battery cell, the positive electrode active material may include a lithium transition metal oxide with the general formula Li a Ni b Co c M d O e A f . 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M includes one or more selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A includes one or more selected from N, F, S, and Cl.
[0123] As an example, the positive electrode active material may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.80 Co 0.15 Al 0.05 One or more of O2.
[0124] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0125] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0126] When the secondary battery is a sodium ion battery cell or a sodium metal battery cell, the positive electrode active material may include but is not limited to one or more of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0127] As an example, the positive electrode active material may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials and general formula X p M' q (PO4) r O x Y 3-x In the general formula X p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes a selection from H + , Li + 、Na + , K + and NH4 +One or more of, M' is a transition metal cation, which may be selected from one or more of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, which may be selected from one or more of F, Cl and Br.
[0128] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.
[0129] In some optional embodiments, the specific surface area of the positive electrode active material satisfies BET of 11 m 2 / g~17m 2 / g. The specific surface area of the positive electrode active material can be 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g or any value thereof. The specific surface area of the positive electrode active material is within the above range, so that it can be more fully mixed with the above dielectric material and other components in the positive electrode active material film layer, which is beneficial for the positive electrode active material in the positive electrode sheet to uniformly deintercalate active ions under the action of the electric field force formed by the dielectric material, thereby improving the deintercalation rate of active ions.
[0130] In some optional embodiments, the average particle size Dv of the positive electrode active material is 1 50 satisfies: 0.2μm~2μm.
[0131] Optionally, the average particle size Dv of the positive electrode active material 1 50 can be any value among 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm or a range of their combinations.
[0132] According to the embodiment of the present application, the average particle size Dv of the positive electrode active material is 1 50 In the above range, it can be mixed with the above dielectric material and other components in the positive electrode active material film layer, and the positive electrode active material is dispersed more evenly, which, on the one hand, improves the flexibility and cohesion of the positive electrode active material film layer, reduces the surface fracture or cracking caused by winding or folding the positive electrode sheet containing the positive electrode active material film layer, and on the other hand, is conducive to the positive electrode active material to uniformly contact with the dielectric material and make the dielectric material store charge, form a polarization electric field, and improve the deintercalation rate of active ions.
[0133] According to the embodiment of the present application, the average particle size Dv of the positive electrode active material is 1 50 In the above range, it is beneficial to the uniform distribution of the positive electrode active material with the dielectric material coated on the surface, and reduces the local temperature change of the dielectric material under the electric field.
[0134] Average particle size distribution Dv 1 50 is a well-known meaning in the art, wherein the particle size distribution Dv 1 50, also known as the average particle size or median particle size, represents the particle size corresponding to 50% of the volume distribution of the positive electrode active material particles; the above particle size distributions can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.
[0135] In some optional embodiments, the thickness d of the coating layer in the cross section of the positive electrode active material is 5nm to 100nm. Alternatively, the thickness of the coating layer can be any value or a range of its composition among 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 15nm, 20nm, 25nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm.
[0136] According to the embodiments of the present application, the thickness of the coating layer is controlled within the above range, and the cycle performance of the battery is improved while reducing the contact area between the positive electrode active material and the electrolyte.
[0137] The average thickness of the coating layer can be calculated by sampling and measuring the average thickness of the coating layer on one side of the cross section of the positive electrode active material.
[0138] In some optional embodiments, the positive electrode active material film layer includes a binder and a conductive agent. When the positive electrode active material film layer has a conductive agent or a binder, the positive electrode active material film layer has a certain cohesive strength, which can improve the flexibility of the positive electrode active material film layer, reduce the probability of fracture or cracking of the positive electrode active material film layer when winding or folding, and at the same time improve the conductivity of the positive electrode plate and reduce the internal resistance of the positive electrode plate.
[0139] In some optional embodiments, the conductive agent is conductive carbon black, and optionally, the average particle size Dv50 of the conductive carbon black is 10nm to 1μm, and optionally 50nm to 500nm. The average particle size Dv50 of the conductive carbon black is within the above range, and can be mixed with the above dielectric material and other components in the positive electrode active material film layer, and the conductive carbon black is more evenly dispersed, which improves the flexibility and cohesion of the positive electrode active material film layer on the one hand, and reduces the surface fracture or cracking caused by winding or folding of the positive electrode sheet containing the positive electrode active material film layer, and on the other hand, it is conducive to the conductive carbon black to uniformly contact with the dielectric material and realize the storage of charge, forming a polarization electric field to increase the deintercalation rate of active ions.
[0140] In some optional embodiments, based on the total mass of the positive electrode active material film layer, the positive electrode active material film layer includes: 85%-98.7% of the positive electrode active material, optionally 91.5%-98.3%.
[0141] The content of the positive electrode active material in the positive electrode active material film layer is within the above range, which is beneficial to increasing the capacity of the battery, improving the energy density of the battery, and thus comprehensively changing the performance of the battery.
[0142] In some optional embodiments, based on the total mass of the positive electrode active material film layer, the positive electrode active material film layer includes: 0.4% to 10% of the conductive agent, optionally 0.7% to 5%.
[0143] The content of the conductive agent in the positive electrode active material film layer is within the above range, which is beneficial to reducing the internal resistance of the positive electrode plate, reducing the internal resistance of the battery cell, facilitating the transfer of electrons, and improving the charge and discharge efficiency of the battery.
[0144] The present application has no particular limitation on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0145] In some embodiments, the positive electrode active material film layer may further optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.
[0146] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0147] The positive electrode active material film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0148] [Method for preparing positive electrode sheet]
[0149] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, the method comprising:
[0150] Providing a slurry comprising a positive electrode active material and a dielectric material, wherein the dielectric constant of the dielectric material is 30 to 3000;
[0151] The slurry is coated on the positive electrode current collector to form a positive electrode active material film layer, thereby obtaining the positive electrode sheet of the first aspect.
[0152] It is understood that the dielectric material may exist in the slurry as a raw material alone, or it may be added separately.
[0153] According to the embodiment of the present application, in the preparation method of the positive electrode sheet, a slurry containing a dielectric material is used to form a positive electrode active material film layer. The electric field formed during the charge and discharge process of the battery excites the dielectric material by the electric field. On the one hand, the positive and negative charges of the dielectric material are arranged separately to generate an electric polarization electric field, thereby driving the Li + / Na + Active ions escape from the positive electrode, accelerating the rate of active ion removal, improving the full capacity charging performance of the battery at room temperature, increasing the charging speed, and being beneficial to the battery's dynamic performance. In addition, as the battery charges and discharges, the dissolved transition metal ions are enriched on the surface of the positive electrode, forming a Li + / Na +The reverse electric field for the escape of active ions, since the positive electrode active material film layer of the positive electrode plate contains dielectric material, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, generating an electric polarization electric field, which can offset the electric field force formed by the enrichment of transition metal ions, thereby improving the lithium / sodium removal performance of the positive electrode plate, which is beneficial to the full charging performance of the battery at room temperature, improving the charging speed, and is beneficial to the battery's kinetic performance.
[0154] On the other hand, the dielectric material is excited by the electric field, and the positive and negative charges of the dielectric material are arranged separately, so it can store a certain amount of charge, which is beneficial to increase the battery capacity and improve the energy density of the battery; because the dielectric material can store a certain amount of charge, it is beneficial to improve the voltage stability of the battery and reduce the voltage drop during the charge and discharge cycle. This helps to maintain the voltage stability of the battery, especially at high discharge rates or low temperature environments.
[0155] In a third aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, the method comprising:
[0156] Providing a slurry containing a positive electrode active material, wherein at least a portion of the surface of the positive electrode active material includes a coating layer, the coating layer includes a dielectric material, and the dielectric constant of the dielectric material is 30 to 3000;
[0157] The slurry is coated on the positive electrode current collector to form a positive electrode active material film layer, thereby obtaining the positive electrode sheet of the first aspect.
[0158] It is understood that the dielectric material can be a part of the surface of the positive electrode active material, added together with the positive electrode active material and exist in the slurry.
[0159] According to the embodiment of the present application, in the preparation method of the positive electrode sheet, at least part of the surface of the positive electrode active material is coated with a dielectric material, which can also improve the de-lithiation / de-sodium performance of the positive electrode sheet, improve the full charging performance of the battery at room temperature, increase the charging speed, and improve the dynamic performance of the battery. It can also increase the energy density of the battery, improve the voltage stability of the battery, and reduce the voltage drop during the charge and discharge cycle.
[0160] As an example, based on the total mass of the positive electrode active material, the conductive agent, and the binder, the total amount of binder added is preferably 1 to 2.5wt%, such as 1wt%, 1.5wt%, 2wt%, and 2.5wt%. If the amount of polymer or binder added is too low, too little binder cannot support the strength of the positive electrode active material film layer, and thus cannot meet the requirements of rolling and thinning. If the amount of binder added is too large, the positive electrode active material film layer will be more viscous, resulting in easy sticking to the roller during the film rolling process, and it is impossible to perform thinning and current collector composite.
[0161] Battery Cell
[0162] In a fourth aspect, an embodiment of the present application provides a battery cell, comprising the positive electrode sheet of the first aspect or the positive electrode sheet manufactured by the method of the second aspect or the third aspect.
[0163] The present application has no particular restrictions on the type of battery cells, for example, the battery cells may be lithium-ion batteries, sodium-ion batteries, etc. Optionally, lithium-ion batteries may be used.
[0164] In some embodiments, a battery cell includes a negative electrode sheet, a separator, and an electrolyte.
[0165] [Negative electrode]
[0166] The specific composition and structure of the negative electrode plate can be selected according to the type of battery cell, and the embodiments of the present application are not limited to this.
[0167] For example, when the battery cell is a lithium-ion battery cell or a sodium-ion battery cell, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0168] The negative electrode active material is a material that can extract and embed active ions (such as lithium ions, sodium ions, etc.), and the negative electrode active material can adopt materials known in the art. As an example, the negative electrode active material includes but is not limited to one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy materials. Tin-based materials may include one or more of elemental tin, tin oxide and tin alloy materials. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials may also be used.
[0169] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0170] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). One or more.
[0171] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC-Na), a PTC thermistor material, and the like.
[0172] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0173] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0174] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the present application may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate of the present application may also include a protective layer covering the surface of the negative electrode film layer.
[0175] When the battery cell is a lithium metal battery cell, the negative electrode plate may not include negative electrode active materials capable of extracting and embedding active ions. For example, in some embodiments, the negative electrode plate may include a lithium plate or a lithium alloy plate; in other embodiments, the negative electrode plate includes a mesh or foam three-dimensional skeleton layer, such as foam copper (or copper alloy), foam nickel (or nickel alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, etc.
[0176] When the battery cell is a sodium metal battery cell, the negative electrode plate may not include negative electrode active materials capable of extracting and embedding active ions. For example, in some embodiments, the negative electrode plate may include a sodium plate or a sodium alloy plate; in other embodiments, the negative electrode plate includes a mesh or foam three-dimensional skeleton layer, such as foam copper (or copper alloy), foam nickel (or nickel alloy), foam aluminum (or aluminum alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, aluminum (or aluminum alloy) mesh, etc.
[0177] [Isolation film]
[0178] The separator is disposed between the positive electrode and the negative electrode, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting. The present application has no particular restriction on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0179] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0180] [Electrolytes]
[0181] In some embodiments, the battery cell includes an electrolyte. The electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).
[0182] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0183] The type of electrolyte salt is not specifically limited and can be selected according to actual needs. For example, the electrolyte salt includes one or more selected from lithium salts for lithium ion batteries and sodium salts for sodium ion batteries. As an example, the lithium salt includes one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate) (LiDFOP), lithium tetrafluorooxalate phosphate (LiTFOP). As an example, the sodium salt includes one or more selected from NaPF6, NaClO4, NaBCl4, NaSO3CF3, Na(CH3)C6H4SO3.
[0184] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0185] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.
[0186] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0187] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0188] [Preparation method]
[0189] The preparation method of the battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through packaging, standing, forming, shaping and other processes.
[0190] The present application has no particular restrictions on the shape of the battery cell, which can be a flat body, a rectangular parallelepiped or other shapes. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0191] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. It is characterized in that the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate together form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 of the first aspect of the embodiment of the present application or the electrode assembly 52 prepared by the method according to the second aspect of the embodiment of the present application is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0192] The preparation method of the battery cell of the present application is well known, and the method at least includes the step of preparing the electrode assembly of the second aspect of the embodiment of the present application. In some embodiments, the electrode assembly can be placed in an outer package, injected with electrolyte after drying, and vacuum packaged, left to stand, formed, shaped, etc. to obtain a battery cell.
[0193] Battery
[0194] In a fifth aspect, an embodiment of the present application provides a battery, comprising the battery cell of the fourth aspect.
[0195] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery or a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0196] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of battery cells are accommodated in the accommodation space.
[0197] In some embodiments, multiple battery modules may be connected in series, in parallel, or in a mixed connection to form a battery pack. In some embodiments, multiple battery cells may directly form a battery pack. The above-mentioned battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0198] Electrical devices
[0199] In a sixth aspect, an embodiment of the present application provides an electrical device comprising the battery of the fifth aspect.
[0200] Battery cells or batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices can be, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0201] Figure 3Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0202] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0203] Example
[0204] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0205] Example 1
[0206] Preparation of positive electrode :LiMn 0.6 Fe 0.4 The positive active material of PO4, the binder polyvinylidene fluoride PVDF, the conductive agent acetylene black SP, and barium titanate (BaTiO3) were mixed at a weight ratio of 97.5:1:1:0.5, and N-methylpyrrolidone (NMP) was added as a solvent. The slurry was stirred in a vacuum state until it was uniform. The obtained slurry was heated to 13.7 mg / cm 2 The surface density is coated on a 13μm aluminum foil with a scraper, and then dried at 140°C, cold pressed, and cut to obtain the positive electrode sheet.
[0207] Preparation of lithium battery monomers
[0208] Positive electrode: as above.
[0209] Preparation of negative electrode sheet: Dissolve the negative electrode active material artificial graphite, conductive agent acetylene black, composite binder SBR, and dispersant sodium carboxymethyl cellulose (CMC-Na) in solvent deionized water at a weight ratio of 97:1:1:1, stir and mix well to prepare negative electrode slurry. 2 The coating density is evenly coated on the 7μm negative electrode collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing and slitting.
[0210] Electrolyte: In an argon atmosphere glove box (H2O <0.1ppm, O2 <0.1ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were evenly mixed in a volume ratio of 3 / 7, 12.5 wt% (based on the weight of the ethylene carbonate / ethyl methyl carbonate solvent) of LiPF6 was added and dissolved in the above organic solvent, and stirred evenly to obtain an electrolyte.
[0211] Separator: A commercially available PP-PE copolymer microporous film with a thickness of 7 μm and an average pore size of 80 nm (from Zhuogao Electronic Technology Co., Ltd., model 20) was used.
[0212] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, the above electrolyte is injected and packaged to obtain a lithium battery monomer.
[0213] Example 2-Example 5
[0214] The difference between Examples 2-5 and Example 1 is that the amount of dielectric material added is different. In Example 2, the positive electrode active material, the binder polyvinylidene fluoride PVDF, the conductive agent acetylene black SP, and barium titanate (BaTiO3) are mixed in a weight ratio of 97:1:1:1. In Example 3, the positive electrode active material, the binder polyvinylidene fluoride PVDF, the conductive agent acetylene black SP, and barium titanate (BaTiO3) are mixed in a weight ratio of 95:1:1:3. In Example 4, the positive electrode active material, the binder polyvinylidene fluoride PVDF, the conductive agent acetylene black SP, and barium titanate (BaTiO3) are mixed in a weight ratio of 93:1:1:5. In Example 5, the positive electrode active material, the binder polyvinylidene fluoride PVDF, the conductive agent acetylene black SP, and barium titanate (BaTiO3) are mixed in a weight ratio of 88:1:1:10.
[0215] Example 6-Example 9
[0216] The difference between Examples 6-9 and Example 1 is that the dielectric constants of the dielectric materials are different, as shown in Table 1.
[0217] Example 10-Example 14
[0218] The difference between Examples 10-14 and Example 1 is that the average particle size Dv50 of the dielectric material is different, as shown in Table 1.
[0219] Example 15-Example 16
[0220] The difference between Examples 15-16 and Example 1 is that the mass content of the dielectric material in the positive electrode active material film layer is different, the dielectric constant of the dielectric material is different, and the average particle size Dv50 is different, as shown in Table 1.
[0221] Comparative Example 1
[0222] The difference between the comparative example 1 and the example 1 is that no dielectric material is added. The positive electrode active material, the binder polyvinylidene fluoride PVDF, and the conductive agent acetylene black SP are mixed in a weight ratio of 97.5:1:1.5.
[0223] Example 17-Example 24
[0224] The differences between Examples 17-24 and Example 1 are: different types of dielectric materials, different dielectric constants of the dielectric materials, and different types of positive electrode active materials, as shown in Table 1.
[0225] Example 25-Example 27
[0226] The difference between Examples 25-27 and Example 17 is that the positive electrode active material, the binder polyvinylidene fluoride PVDF, and the conductive agent acetylene black SP are mixed at a weight ratio of 98:1:1. The positive electrode active material includes a coating layer on the surface. The thickness of the coating layer of Examples 25-27 is 40, 50, and 70 nm, respectively, and the component of the coating layer is a dielectric material. The type of dielectric material, the thickness of the coating layer, and the average particle size of the positive electrode active material are shown in Table 1.
[0227] Example 28-Example 30
[0228] The difference between Examples 28-30 and Example 1 is that the types of positive electrode active materials are different and the particle sizes of the positive electrode active materials are different, as shown in Table 1.
[0229] Example 31-Example 35
[0230] The difference between Examples 31-35 and Example 1 is that the types of positive electrode active materials are different, as shown in Table 1.
[0231] Example 36-Example 38
[0232] The difference between Examples 36-38 and Example 1 is that the types of positive electrode active materials are different, and the preparation of the battery body is different. Others are shown in Table 1.
[0233] Preparation of sodium battery battery in Example 36-38: The positive electrode active material, the conductive agent acetylene black SP, the binder polyvinylidene fluoride PVDF, and barium titanate (BaTiO3) were mixed in a weight ratio of 97.5:1:1:0.5, N-methylpyrrolidone (NMP) was added as a solvent, and the slurry was stirred in a vacuum state until it was uniform. The obtained slurry was heated to 13.7 mg / cm 2 The surface density is coated on a 13μm aluminum foil with a scraper, and then dried at 140°C, cold pressed, and cut to obtain the positive electrode sheet.
[0234] Preparation of negative electrode plates: Add carbon nanotubes and sodium alginate into deionized water and stir to form a uniform slurry, apply the slurry on copper foil, cut the plates after drying and cold pressing, assemble the plates with positive electrode plates and isolation membrane into battery cells, charge the assembled battery cells at a constant current of 0.5C to 3.8V, so as to pre-deposit sodium metal on the plates; after the battery cells are fully charged, remove the fully charged plates in the glove box as negative electrode plates.
[0235] Isolation film: A commercially available glass fiber film with a thickness of 7 μm was used as the isolation film;
[0236] Assembly of battery cells: stack the above-mentioned positive electrode sheets, glass fiber films and negative electrode sheets in order, and form an electrode assembly after winding. Put the electrode assembly into a packaging shell, add a 1M NaPF6 electrolyte, and obtain a sodium metal battery after packaging, formation, standing and other processes.
[0237] Test Section
[0238] The battery cells prepared in the examples and comparative examples were subjected to performance testing, and the specific testing methods are as follows.
[0239] 1) Method for detecting the average particle size of dielectric materials and positive electrode active materials: Use SEM electron microscope to scan the cross section of the electrode piece to measure the average particle size of the dielectric material and the positive electrode active material.
[0240] 2) Method for testing the mass content of dielectric materials in the positive electrode active material film layer: sample the electrode coating, and use thermogravimetric analysis (TG) to measure the weight of the dielectric material and other electrode components. Alternatively, use inductively coupled plasma spectrometer (ICP) to analyze the content of each element of the electrode sample to obtain the mass of the dielectric material and other component materials.
[0241] 3) Detection method of dielectric material and positive electrode active material types: Determine by X-ray diffraction pattern XRD and mass spectrometry. Or use SEM electron microscope to scan the surface of the electrode, select the active material and coating layer area respectively, and use EDX to perform elemental analysis to determine the types of dielectric material and active material.
[0242] 4) Method for detecting coating thickness: Scan the electrode cross section with a SEM electron microscope to measure the thickness of the coating layer coated on the particle surface.
[0243] 5) Detection method of gram capacity of positive electrode active material: After the obtained button cell is left to stand for 12 hours, it is discharged at a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 50μA to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 10μA to 0.005V; then it is charged at a constant current of 0.1C to 2V, and the charging capacity is recorded. The ratio of the charging capacity to the mass of the positive electrode active material is the gram capacity of the positive electrode active material.
[0244] 6) Internal resistance (DCR) performance test: At 25°C, charge at 0.33C to full charge, then discharge at 0.33C for 0.5Cn (Cn represents battery capacity) to adjust the battery cell to 50% SOC, let stand for 30 minutes, end stand voltage V1, then discharge at 3C for 30 seconds, end discharge voltage V2, then discharge at 3C for 30 seconds, let stand for 40 seconds, and charge at 3C for 30 seconds;
[0245] Calculation method: DCR = (V1-V2) / I, where V1 is the static end voltage, V2 is the discharge cut-off voltage, and I is the discharge current. The test results are shown in Table 1.
[0246] (7) Method for testing the initial coulombic efficiency of a battery
[0247] A brand new battery that has not undergone a complete charge and discharge cycle is charged at 0.33C to 3.65V at a constant voltage of 0.05C at 25°C, the charge capacity is recorded, and the battery is allowed to stand for 30 minutes. The battery is discharged at 0.33C to 2.5V and the discharge capacity is measured during the period, and the battery is allowed to stand for 30 minutes. The coulombic efficiency is calculated by calculating the ratio of the discharge capacity to the charge capacity.
[0248] (8) Maximum charge SOC / % of the battery at 25°C: At 25°C, charge to 3.65V at 0.33C and charge at a constant voltage until the current reaches 0.05C, record the charge capacity C1, and let it stand for 30 minutes. At 25°C, discharge to 2.5V at 0.33C and let it stand for 30 minutes. At 40°C, charge to 3.65V at 0.33C and charge at a constant voltage until the current reaches 0.05C, record the charge capacity C2, and let it stand for 30 minutes. At 25°C, discharge to 2.5V at 0.33C and let it stand for 30 minutes. The maximum charge SOC of the battery at 25°C is the percentage of the ratio of the charge capacity C1 at 25°C to the charge capacity C2 at 40°C.
[0249] The test results are shown in Table 1.
[0250] From the test results in Table 1, it can be seen that the positive electrode sheets containing dielectric materials in Examples 1-16 have higher gram capacity, and the batteries containing the positive electrode sheets have higher first coulombic efficiency, cell internal resistance, and better full charge rate at room temperature. Further, in Examples 1 and 6-9, as the dielectric constant of the dielectric material increases, the first coulombic efficiency and cell internal resistance of the battery are relatively reduced; further, Examples 11-14 show that the larger the average particle size Dv50 of the dielectric material, the lower the first coulombic efficiency, cell internal resistance, and full charge rate at room temperature of the battery.
[0251] Compared with Examples 1-16, Comparative Example 1 does not add a dielectric material with a suitable dielectric constant to the positive electrode plate. The battery containing the positive electrode plate has relatively low first coulomb efficiency, cell internal resistance and full charge rate at room temperature.
[0252] The types of dielectric materials and positive electrode active materials added in Examples 17 to 24 are different, and relatively better first coulombic efficiency, battery cell internal resistance and better full charge rate at room temperature are also obtained.
[0253] In Examples 25-27, the surface of the positive electrode active material is coated with a dielectric material of different types, so that the battery obtains a relatively better first coulombic efficiency, a cell internal resistance and a better full charge rate at room temperature.
[0254] In Examples 28-30, the average particle size DV50 of the positive electrode active material is different from that in Example 1, so that the battery obtains relatively better first coulomb efficiency, cell internal resistance and better full charge rate at room temperature.
[0255] In Examples 31-38, the types of positive electrode active materials are different from those in Example 1, so that the batteries obtain relatively better first coulombic efficiency, cell internal resistance and better full charge rate at room temperature.
[0256] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
[0257]
[0258]
Claims
1. A positive electrode sheet, characterized in that: The positive electrode plate comprises: a positive electrode current collector and a positive electrode active material film layer arranged on at least one side of the positive electrode current collector, the positive electrode active material film layer comprises a positive electrode active material and a dielectric material, and the dielectric constant of the dielectric material is 30 to 3000.
2. The positive electrode sheet according to claim 1, characterized in that: The dielectric constant of the dielectric material is 90-2000, and can be optionally 1200-1800.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The mass content of the dielectric material in the positive electrode active material film layer is 0.5% to 10%.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The dielectric material includes a ferroelectric material.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The dielectric material includes one or more of barium titanate, zirconium titanate, barium strontium titanate, lead titanate, lithium niobate, lead zirconate titanate, lead metaniobate, lithium lead barium niobate, titanium zirconium oxide, zirconium ferrite, and bismuth ferrite; optionally, it includes one or more of lithium lead barium niobate, titanium zirconium oxide, zirconium ferrite, bismuth ferrite, barium strontium titanate, and zirconium titanate.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The average particle size Dv of the dielectric material 1 50Satisfies 1nm<Dv 1 50<1500nm, optionally, 10nm<Dv 1 50<1000nm.
7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: At least part of the surface of the positive electrode active material includes a coating layer, and the coating layer contains the dielectric material; optionally, the average particle size Dv of the positive electrode active material 2 The ratio of 50 to the thickness d of the coating layer on the positive electrode active material is (2-120):1, and can be optionally (4-100):
1.
8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The positive electrode active material includes one or more of a metal oxide material and an olivine positive electrode material; optionally, the metal oxide material includes one or more of a layered metal oxide material and a spinel material; optionally, the olivine positive electrode material includes a lithium iron manganese phosphate material.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The positive electrode active material satisfies at least one of the following conditions: 1) The specific surface area of the positive electrode active material satisfies BET of 11 m 2 / g~17m 2 / g; 2) The average particle size Dv of the positive electrode active material 1 50: 0.2μm~2.0μm; 3) The coating layer has a thickness d of 5 nm to 100 nm in the cross section of the positive electrode active material.
10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The positive electrode active material film layer includes a binder and a conductive agent; Optionally, the conductive agent is conductive carbon black, and optionally, the average particle size Dv50 of the conductive carbon black is 10 nm to 1 μm, and optionally 50 nm to 500 nm.
11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: The positive electrode active material film layer satisfies at least one of the following conditions: Based on the total mass of the positive electrode active material film layer, the positive electrode active material film layer includes: 85%-98.7% of positive electrode active material, optionally 91.5%-98.3%; Based on the total mass of the positive electrode active material film layer, the positive electrode active material film layer includes: 0.4% to 10% of the conductive agent, and optionally 0.7% to 5%.
12. A method for preparing a positive electrode sheet, characterized in that: Methods include: Providing a slurry comprising a positive electrode active material and a dielectric material, wherein the dielectric constant of the dielectric material is 30 to 3000; The slurry is coated on a positive electrode current collector to form a positive electrode active material film layer, thereby preparing the positive electrode sheet according to any one of claims 1 to 11.
13. A method for preparing a positive electrode sheet, characterized in that: Methods include: Providing a slurry containing a positive electrode active material, wherein at least a portion of the surface of the positive electrode active material comprises a coating layer, the coating layer comprises the dielectric material, and the dielectric constant of the dielectric material is 30 to 3000; The slurry is coated on a positive electrode current collector to form a positive electrode active material film layer, thereby preparing the positive electrode sheet according to any one of claims 1 to 11.
14. A battery cell, characterized in that: The invention comprises the positive electrode sheet according to any one of claims 1 to 11 or the positive electrode sheet made by the method according to claim 12 or 13.
15. A battery, characterized in that: Comprising the battery cell according to claim 14.
16. An electrical device, characterized in that: Comprising the battery of claim 15.